Management of Pararenal Aortic Aneurysms : A Literature Review - Ibrahim, Hilman; muradi, akhmadu; Fachriza, Ihza (UI Scholars Hub, 2021)
Abdominal aortic aneurysms (AAA) are the most common group of aortic aneurysms. Pararenal aortic aneurysm (PAA) is a classification of AAA where there is no normal aortic segment between the renal artery and the proximal border of the aneurysm. This group has a prevalence of around 20% of all AAA cases. In open repair (open surgery), PAA requires suprarenal clamps or even supraceliac which causes high morbidity. In endovascular procedures, PAA presents difficulties due to the absence of a landing zone to place the graft and the possibility of reintervention after action. A literature review is needed to discuss the strengths and weaknesses of each treatment. A review enrolling 7 focused on endovascular procedures for PAA and outcomes including mortality and morbidity with long-term follow-up